Graphene semiconductor superhydrophobic coating with stretchability - HUAI Jiru; WANG Peng; YANG Mengyu (Hangkong gongcheng jinzhan)
Superhydrophobic coating is the ideal anti-icing materials, and the superhydrophobic materials can delay the formation of ice crystals or reduce the strength of ice adhesion, but the existing coating has the problems such as poor mechanical property and fast natural aging of performance parameters. The modified graphene is partially embedded into the elastomer to produce a new coating. The icing-deicing performance of the coating is tested and compared, and the surface structure and chemical composition of the coating are analyzed. The results show that the new coating has a certain ability of electric deicing. In the re-mechanical properties test, the coating showed excellent properties in strain, wear resistance and aging resistance. The graphene introduced into the coating is the key to make the coating have a certain active deicing ability. The unique active and passive dual deicing properties of the coating are different from the traditional passive coating unique properties, which not only lays the foundation for the research and development of dual-attribute anti-icing coating but also opens up a new development direction of anti-icing coating.